Nutrition and wound healing - Molnar, Joseph Andrew (CRC series in modern nutrition science., 2006)
With mounting evidence regarding the role of poor nutrition in the development of chronic diseases such as heart disease and diabetes, it is no secret that appropriate nutrition is crucial to optimal health. Achieving the correct balance of elements provides the body with the ability to adapt to a shifting and often hazardous environment. Never is this capability more important than when a wound is sustained and the body's first line of defense, the skin, is breached.Nutrition and Wound Healing describes the importance of several nutrients, both macronutrients and micronutrients. - Resumé vydavatel